Sebuah Optimalisasi Implementasi Offset Defense sebagai Upaya Pemenuhan dalam Material dan Teknologi Pesawat Tempur - Gunawan, Hendra; Khaerudin, Khaerudin; George Royke Deksino; Rudy AG Gultom (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to investigate the implementation of defense offset as a strategy to address the gap in the supply of materials and technology for fighter aircraft among countries. In this context, the gap arises due to the complexity and high costs associated with fighter aircraft development. Many countries, particularly those with limited technological and manufacturing capabilities, face challenges in acquiring and developing advanced aircraft. This gap negatively impacts their defense capability enhancement efforts. Therefore, the concept of defense offset emerges as a potential solution. Defense offset is a strategy in which foreign aircraft manufacturers provide compensation in the form of technology transfer, investment in the local defense industry, or research and development collaboration to the purchasing country. Through steps such as identifying material and technological needs, planning clear offset agreements, transferring relevant technology, developing the local industry, supplying materials, research and development collaboration, as well as monitoring and evaluation, the implementation of defense offset can be optimized. This research employs a qualitative method with a descriptive approach, involving a literature study to gain in-depth information about defense offset implementation and its impact on the material and technology gap in fighter aircraft. The results include the identification of factors influencing the success of defense offset implementation, political, economic, and strategic implications, as well as the benefits obtained by purchasing countries. In conclusion, through the optimization of defense offset, purchasing countries can reduce the gap in materials and technology for fighter aircraft, enhance domestic defense industry, and strengthen national defense capabilities. With the right strategy, defense offset can be an effective tool in addressing the gap in fighter aircraft material and technology, thereby fortifying national defense.